Enhanced Particle Swarm Optimization for Automated Compatibility Testing in Cloud-based Distributed Systems - Li, Dai; Lan, Weishuo (Journal of Cross-Disciplinary Sustainability Innovations, 2025)
Ensuring software compatibility in cloud-based distributed systems presents significant challenges due to the heterogeneous nature of cloud environments and the complexity of distributed architectures. This paper proposes an enhanced particle swarm optimization (PSO) approach for automated compatibility testing that addresses the limitations of traditional testing methods. The methodology integrates improved PSO algorithms with TLA+ formal verification and Jepsen distributed testing frameworks, incorporating dispersion adjustment mechanisms to prevent premature convergence and enhance testing coverage. Key improvements include adaptive weight adjustment, collision radius optimization, and fitness function modification based on branch path coverage metrics. Experimental validation demonstrates significant improvements in compatibility testing efficiency, coverage breadth, and system robustness across diverse cloud computing environments. The proposed approach effectively optimizes software performance and reliability while ensuring seamless operation of distributed systems in dynamic cloud infrastructures.